The Role of Intrinsic Motivation on Altruism, Civic Virtue, Affective Commitment and Work Engagement - Muchtadin; Sundary, Zelvy Emmelya (Research of Economics and Business, 2023)
Intrinsic motivation plays a pivotal role in shaping various dimensions of nursing practice. This study investigates how intrinsic motivation influences altruism, civic virtue, affective commitment, and work engagement among Bakti Timah Medika nurses. A sample of 134 nurses was selected through accidental sampling. This research uses a quantitative approach to analyze Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal a significant positive correlation between intrinsic motivation and altruism, civic virtue, affective commitment, and work engagement. Notably, work engagement demonstrates the most substantial impact of intrinsic motivation. Furthermore, this study suggests a potential mediator role of work engagement between inherent motivation and altruism, civic virtue, and affective commitment. By shedding light on the influence of intrinsic motivation on essential work outcomes (altruism, civic virtue, affective commitment, and work engagement) within the health sector, this research contributes to enhancing nursing practices.